The Rule of Organic Fertilizer on Fertilizer Efficiency and Requirement Rate for Vegetable Crop on Inceptisols Ciherang, Bogor (JOURNAL OF TROPICAL SOILS, 2009)
Utilization of organic fertilizer is an alternative to increase soil health and supply a small amount of plant nutrient. Meanwhile agricultural soil in Indonesia commonly have low organic carbon content (
Keywords: Agronomic effectiveness; Inceptisols; nitrogen; NPK; organic fertilizer